Case Assignment in Agrammatism - Ruigendijk, Esther; Zonneveld, Ron van; Bastiaanse, Roelien (Journal of speech, language, and hearing research, 1999)
Agrammatic speech is characterized by the omission and substitution of grammatical morphemes. Some recent papers suggest that certain patterns of omission and substitution are ruled by linguistic, that is, syntactic processes (e.g., Hagiwara, 1995; Friedmann & Grodzinsky, 1997; Bastiaanse & Van Zonneveld, 1998). In the present paper, the omission pattern of case markers in the spontaneous speech of Dutch and German speakers with agrammatic aphasia is analyzed within the framework of Chomsky's (1986) case theory , which says that every phonetically realized NP must receive (abstract) case. The inflected verb (I) assigns nominative case to the subject in the sentence, and the verb (V) assigns dative and accusative case to the indirect and direct object, respectively. This, in combination with the knowledge that verbs and verb inflections are notoriously difficult for speakers with agrammatism, served as the basis for this study. We hypothesize that, if no case assigner is produced, the noun will receive nominative case by default or the case marking morpheme (i.e., the determiner) will be omitted. This hypothesis has been tested and was supported by the data.